Comparison of Civic Education in Hong Kong and Indonesia in The Context of History and Educational Curriculum - Idham Mahdi; Muhammad Syamsuddin; Sunarso Sunarso (PT Publikasiku Academic Solution, 2025)
This study compares the civic education systems in Hong Kong and Indonesia, analyzing their historical development, curriculum structures, and educational goals. The research employs a literature review approach, utilizing secondary sources such as academic books, peer-reviewed journals, and policy documents to compare the educational frameworks of both regions. The findings reveal that Hong Kong’s civic education has evolved within the context of its transition from British colonial rule to becoming a Special Administrative Region of China, with a focus on fostering national identity and legal compliance under the “One Country, Two Systems” framework. In contrast, Indonesia’s civic education has developed in response to its independence, emphasizing Pancasila, the 1945 Constitution, and democratic values. The study identifies key differences in curriculum content, evaluation systems, and learning objectives, showing how each country’s civic education reflects its socio-political environment. The research underscores the importance of contextualizing civic education in the formation of responsible citizens who are equipped to address global challenges. This comparative study offers valuable insights for enhancing civic education curricula in both countries and globally.